Effect of Probiotics Bacillus subtilis on Feed Efficiency and Egg Mass of Laying Hens - Pratama, Hanif Sabekti; Lokapirnasari, Widya Paramita; Soeharsono, Soeharsono; Al-Arif, Muhammad Anam; Harijani, Nenny; Hidanah, Sri (Jurnal Medik Veteriner, 2021)
The aim of this research was to investigate the effect of probiotics Bacillus subtilis on feed efficiency and egg mass of laying hens. This research was using 36 of 38 weeks-old laying hens Isa Brown strain. The concentration of probiotics B. subtilis was 1 x 109 CFU/ml, there were three kinds of treatments, P0 (without given probiotics B. subtilis), P1 (given 0.1 gram of probiotics B. subtilis per kg of feed), and P2 (given 0.2 gram of probiotic B. subtilis per kg of feed). The results of feed efficiency, the provision of probiotics can provide a significantly different values (p <0.05) between treatments either P0, P1, or P2. Provision probiotics P1 showed the highest value of feed efficiency (81.72 ± 5.28), while the lowest value at P0 was (64.06 ± 3.30). The results showed that there were significantly different in egg mass values (p <0.05) between treatments both P0, P1, and P2. Probiotic P2 shows the highest value (53.30 ± 2.13), while the lowest egg mass value of probiotics is as much as P1 (40.83 ± 4.73). Based on the results of this study it can be concluded that the B. subtilis probiotics both at a dose of 0.1 gram / kg of feed and a dose of 0.2 gram / kg of feed can affect the growth performance of laying hens.